Adoption of Information Technology and its Relative Contribution to a Firm's Agility - Masrom, Maslin (2003)
In the world of business, information technology (IT) continues to heighten competencies and ensure success of firms. But, investment in the emerging IT can lead to productivity gains only if it is accepted and effectively used. As a consequence, IT acceptance and utilization represent central concerns in recent information systems research. Therefore, the main objective of this research is to examine the influence of external variables on IT acceptance (Le., usage), and how IT acceptance contributes to a firm's ability to be an agile competitor. This research is an empirical attempt to investigate the influence of IT acceptance and usage on agility, based on a well-established theoretical model, that is, Technology Acceptance Model (TAM) from the management information system area. TAM was chosen as the theoretical basis (paradigm) within which an extended model was formulated. A few adaptations to this paradigm were introduced in order to make them applicable to the present context building upon, and integrating previous researches in a cumulative manner. This led to a research and integrating previous researches in a cumulative manner. This led to a research model which was tested by a seventeen-page survey questionnaire. This research used results from a survey among 329 managers and executives in manufacturing firms in the Klang Valley, Malaysia. A careful confirmatory factor analysis (CFA) and a reliability analysis (Cronbach's alpha coefficient) for the measure used in the survey were conducted. Correlation analysis, multiple regression analysis, and structural equation modeling (SEM) analysis using AMOS 4.0 were used as different data analysis techniques. The analysis in part gave good support for the initial model considered, but also revealed some shortcomings in the base model (TAM). The findings from this research indicated that information quality is a dominant factor in explaining agility, followed by top management support. The results also indicated that perceived usefulness has a strong effect on actual system use. Similarly, the results also indicated that exogenous variables (independent variables) influence actual system use, particularly system characteristics, job characteristics and top management support. The results then revealed that actual system use mediated the relationships between these exogenous variables and agility. The findings have several implications for information system (IS) management practice. Thus, implications for the acceptance of IT and agility, for theory and practice that follow, and future research are also discussed.